PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI KESEJAHTERAAN KARYAWAN - Putra, Dony Syah; Kumbara, Vicky Brama; Charli, Chintya Ones (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This study aims to find out how much influence leadership style, work discipline and employee welfare, both partially and gradually, have on employee performance at PT. Kilang Lima Gunung. The data collection method uses surveys and distributing questionnaires, with a sample of 133 respondents at PT. Kilang Lima Gunung. The analytical method used is the descriptive variable analysis method. The test results obtained based on the partial test (t test) showed: (a) partially there is a positive and insignificant influence between leadership style on employee welfare. (b) partially there is a positive and significant influence between work discipline on employee welfare. (c) partially there is no positive and insignificant influence between leadership style on employee performance. (d) partially there is a positive and significant influence between work discipline on employee performance. (e) partially there is a positive and significant influence between employee welfare on employee performance. (f) partially employee welfare is unable to mediate the relationship between leadership style and employee performance. (g) partially employee welfare is able to mediate the relationship between work discipline and employee performance. So the author concludes that leadership style, work discipline and employee welfare simultaneously and partially influence improving employee performance.